Circulating metabolites and the development of type 2 diabetes in Chinese adults - Bragg, F; Kartsonaki, C; Holmes, M; Du, H; Yang, L; Chen, Y; Schmidt, D; Avery, D; Clarke, R; Hill, M; Millwood, I; Chen, Z (American Diabetes Association, 2021)
Objective: To assess prospective associations of circulating metabolites with risk of type 2 diabetes (T2D) among Chinese adults.